Slag, limestone, and urea application in latosol cultivated with rice - Vidal, Anelisa de Aquino; Prado, Renato de Mello [UNESP] (My University, 2011)
Slag is a calcium silicate and silicon source, whose corrective action on soil is similar to the limestone one. Despite its corrective and fertilizing potential, there is little information about its effects on soil chemical attributes. The study evaluated the effects of the slag, limestone, and urea application on the chemical attributes of a Brazilian Oxisol cultivated with rice. The treatments consisted of two corrective agents sources (limestone and slag), with three doses (1.3 g dm-3, 2.6 g dm-3, and 5,2 g dm-3); three N doses (80 mg dm-3, 160 mg dm-3, and 320 mg dm-3), applied as urea; and a control, arranged in randomized blocks, in a factorial scheme, with four replications. Ninety days after the soil incubation and 120 days after planting, soil samples were collected for chemical analysis. The slag was efficient in correcting soil acidity, and nitrogen fertilization contributed to increment acidity in the soil cultivated with rice, decreasing base saturation, as well as the Ca and Mg content. The slag application improved silicon availability, however, when associate to the nitrogen fertilization, the silicon content in the soil did not change.
Aplicação de escória siderúrgica, calcário e ureia em latossolo cultivado com arroz
Keywords: Nitrogen fertilization; Oriza sativa L.; Soil acidity; Steel waste